Implementasi Pendidikan Karakter Menanamkan Nilai-Nilai Karakter melalui Kegiatan Keagamaan di TK Muslimat NU 29 Mahkota Gresik - Hasanah, Muhimmatul (Proceedings of Annual Conference for Muslim Scholars, 2019)
Education is a very important role to ensure the survival of the state and nation. Wherever, character building is a very important national foundation and needs to be instilled early on in children. Therefore, it is very important to shape character values ​​through habituation and religious activities that begin at an early age. This study aims to: (1) Implementation of early childhood character education through religious activities in Muslimat NU 29 Mahkota Gresik Kindergarten, (2) Knowing the values ​​of character education for children who are implanted in Muslimat NU 29 Mahkota Gresik Kindergarten. The result show that the implementation of student character education through religious activities has been going well in accordance with the program that has been determined through several activities both habituation and exemplary. Religious activities that are routinely carried out every day include infaq, reading Asmaul Husna, reading prayers before entering class, reciting prayers, listening activities and memorizing short letters, and studying prayer. The character values ​​instilled through religious activities are religious, discipline, responsibility, honesty, fond of reading, social care, and communicative